The Suakin Dilemma: Conservation and Heritage Management in Eastern Sudan. (3rd April 2015) - Breen, Colin; Rhodes, Daniel; Forsythe, Wes
Abstract : For much of the second millennium CE Suakin was one of the most important port cities in the upper Red Sea region. Effectively abandoned in the late 1920s, the historic core of the urban centre has deteriorated to such an extent that it now consists of little more than a pile of rubble. How, then, does a heritage professional approach the future management or development of a site like this? A range of options are presented here in an attempt to generate a more informed and engaged approach to the site's future. Underpinning this research is an assumption that heritage conservation is an integral part of civil society and that conservation both contributes to the nature of, and in turn is shaped by, the needs and forces of that society.